“Ocean Grabbing!”: Perampasan Hak-Hak Nelayan atau Hak-Hak Pengelolaan Sumberdaya Pesisir dan Kelautan - Jeanne Darc Noviayanti Damanik; Wirazilmustaan Wirazilmustaan (Society, 2021)
The state is obliged to strive for the realization of justice for traditional fishing communities. Traditional communities are fishing communities whose traditional rights are still recognized in carrying out fishing activities or other legal activities in certain areas located in archipelagic waters following the international law of the sea. Coastal space areas and small islands that indigenous/traditional communities have managed from the obligation to have location permits and management take national interests and laws and regulations into account. Article 26 A of the Republic of Indonesia Number 1 of 2014 makes it easy for outsiders to control small islands that regulate the use of small islands and surrounding coasts through investment forms based on a ministerial permit that must prioritize the national interest. Positive law must protect traditional fishing communities and indigenous peoples. This research aims to analyze the regulation of fishermen’s protection from deprivation of their rights in earning a living and livelihood. The research method used is normative research, meaning the implementation of legal provisions in the form of legislation in activities for certain legal events in the community, especially the fishing community. Normative research refers to and examines laws and regulations related to the research being conducted. The research locations cover coastal areas throughout Indonesia, especially Banda Aceh, Padang, Jakarta, Semarang, Surabaya, Manado, Kupang, Ternate, and Mataram. The state can provide knowledge, guidance, and protection for fishermen from various actions of deprivation of their rights to earn a living and protection such as piracy, the practice of fishing theft, abuse of trawling, transshipment activities, threats, and violence by foreign parties to Indonesian fishers. The central government and local governments are obliged to provide facilities for guaranteeing fishing areas or fishing coverage areas that are safe and do not overlap with other fields.